2022
DOI: 10.15587/2519-8025.2022.271043
|View full text |Cite
|
Sign up to set email alerts
|

Some biological, behavioral and social aspects of the perfumery use in the Ukrainian population sample (part 1. age associations)

Abstract: The aim. The study encompassed some aspects related to perfumes use, which can potentially influence the individual perfume choice, in particular, among different age groups of the Ukrainian population. Factors related to perfumes choice, the state of awareness of respondents regarding quality, safety, and existing stereotypes regarding the characteristics of perfumes and potential harmful effects on the human body were investigated. Materials and methods. The analysis was performed on a sample of 124 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, there is no significant association between specific factors of perfume choice and education level. In the preliminary study of the relationship between age and the factors of perfume choice, we found that although people, regardless of age, are also more likely to focus on a certain fragrance, still, in older age groups, the focus on brand perfumes is increasing, but this association had a statistically significant pattern [4]. In the current research, it is also possible to trace, that with an increase in the education level, the role of the brand factor increases, but only at the level of the trend.…”
Section: Associations Of Education Level and Factors Related To Perfu...mentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, there is no significant association between specific factors of perfume choice and education level. In the preliminary study of the relationship between age and the factors of perfume choice, we found that although people, regardless of age, are also more likely to focus on a certain fragrance, still, in older age groups, the focus on brand perfumes is increasing, but this association had a statistically significant pattern [4]. In the current research, it is also possible to trace, that with an increase in the education level, the role of the brand factor increases, but only at the level of the trend.…”
Section: Associations Of Education Level and Factors Related To Perfu...mentioning
confidence: 83%
“…We developed a questionnaire [4] in a Google form, which was sent to the respondents to their email inboxes. The questionnaire contained 15 questions related to the attitude to perfumes, the respondents' awareness of perfumes composition, the content of harmful ingredients, the persistence of the smell, and the impact on human health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation